Partner Selection in R&D Collaborations: Effects of Affiliations with Venture Capitalists - Reuer, Jeffrey J.; Devarakonda, Ramakrishna (Organization Science, 2017)
This paper extends information economics to the literature on alliance partner selection by demonstrating how venture capitalists (VCs) can facilitate research and development (R&D) collaborations. We investigate a new role for VCs—information intermediation—that can enable R&D partnerships between entrepreneurial ventures that lack knowledge of each other’s technological resources. In contrast to the more diffuse signaling benefits entrepreneurial ventures obtain by affiliating with prominent VCs, backing by a common VC can privately and directly reduce information asymmetries between entrepreneurial ventures. We demonstrate that the effects of VC information intermediation are more pronounced when prospective collaborators are at the earliest stages of product development and when they find it difficult to judge each other’s technological resources, such as when they do not have previous partnerships together, do not draw upon each other’s knowledge bases, and have dissimilar technology portfolios. We empirically investigate the multiple ways in which VCs potentially facilitate R&D partner selection and identify specific conditions under which VCs’ information intermediation function contributes to segmentation in markets for R&D alliances.